Native and exotic oysters in Brazil: comparative tolerance to hypercapnia - Moreira, Anthony (2020)
Environmental hypercapnia in shallow coastal marine ecosystems can be exacerbated by increasing levels of atmospheric CO2. In these ecosystems organisms are expected to become increasingly subjected to pCO2 levels several times higher than those inhabiting ocean waters (e.g.: 10,000 µatm), but still our current understanding on different species capacity to respond to such levels of hypercapnia is limited. Oysters are among the most important foundation species inhabiting these coastal ecosystems, although natural oyster banks are increasingly threatened worldwide. In the present study we studied the effects of hypercapnia on two important oyster species, the pacific oyster C. gigas and the mangrove oyster C. brasiliana, to bring new insights on different species response mechanisms towards three hypercapnic levels (ca. 1,000; 4,000; 10,000 µatm), by study of a set of biomarkers related to metabolic potential (electron transport system - ETS), antioxidant capacity (SOD, CAT, GSH), cellular damage (LPO) and energetic fitness (GLY), in two life stages (juvenile and adult) after 28 days of exposure. Results showed marked differences between each species tolerance capacity to hypercapnia, with contrasting metabolic readjustment strategies (ETS), different antioxidant response capacities (SOD, CAT, GSH), which generally allowed to prevent increased cellular damage (LPO) and energetic impairment (GLY) in both species. Juveniles were more responsive to hypercapnia stress in both congeners, and are likely to be most sensitive to extreme hypercapnia in the environment. Juvenile C. gigas presented more pronounced biochemical alterations at intermediate hypercapnia (4,000 µatm) than C. brasiliana. Adult C. gigas showed biochemical alterations mostly in response to high hypercapnia (10,000 µatm), while adult C. brasiliana were less responsive to this environmental stressor, despite presenting decreased metabolic potential. Our data bring new insights on the biochemical performance of two important oyster species, and suggest that the duration of extreme hypercapnia events in the ecosystem may pose increased challenges for these organisms as their tolerance capacity may be time limited.